The legal protection of Indonesian domestic workers in Malaysia - Nur Chaerani (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2008)
The abuse of domestic workers is a global disgrace, taking place in many countries including Malaysia as top destination in South East Asia for migrant domestic workers especially from Indonesia. Types of abuse that domestic workers (many of whom are Muslims and from Indonesia) experience in Muslim countries like Malaysia are physical, psychological and sexual violence. Without legal protection from receiving country, domestic workers are particularly vulnerable to exploitation and abuses from the recruitment agencies to the employer. Domestic workers who work in Malaysia are excluded from key protections in Malaysia's main labour laws under part XII of the Employment Act 1995. Gaps in labour laws and punitive immigration policies have left many migrants at risk of abuses and labour exploitation by employers and recruitment agencies. Indonesia and Malaysia signed a Memorandum of Understanding (MOU) in May 2006 to regulate migration of domestic workers. Positive measures included the introduction of a standard contract and protections against cutting workers' salaries to repay fees borne by the employer. However, it allows employers to keep workers' passports, prohibits workers from marrying, and fails to introduce clear standards on a minimum wage, a weekly day off, or monitoring mechanisms for labour agencies. This thesis therefore discuss and analyze the need of legal protection for Indonesian domestic workers in Malaysia from Chapter 2 to 4, of which will include the International legal framework toward migrant domestic workers and its definition to evade the existing ambiguity. It will further highlight the procedure and process of handling Indonesian domestic workers in Indonesia and Malaysia and the dispute that arise among the employer, employee and the Agency. Chapter 5 discusses on the Islamic principles regulating and giving legal protection toward these workers. Finally, Chapter 6 concludes the research by giving some relevant recommendations.